Numerical Simulation of the Flow and Heat Transfer Characteristics of Sweeping and Direct Jets on a Flat Plate with Film Holes - Xiangcan Kong; Yanfeng Zhang; Guoqing Li; Xingen Lu; Junqiang Zhu; Jinliang Xu (Energies, 2022)
The internal heat transfer performance and flow structures of a sweeping jet and film composite cooling on a flat plate were numerically studied. Sweeping jet and film composite cooling consists of a fluidic oscillator and 20 cylindrical film holes; the direct jet is formed by removing the feedback from the fluidic oscillator, which is different from the traditional cylindrical nozzle. Four different mass flow rates of coolant were considered, and the inclination angle of the film hole was 30°. The Conjugate Heat Transfer method (CHT) and Unsteady Reynolds Averaged Navier Stokes equation (URANS) were employed. The results indicated that the flow resistance coefficients of the sweeping jet were larger than those of the direct jet, and the Nusselt number monotonously increased with the increase in the mass flow rate. Compared to the direct jet, the sweeping jet had a more spatially uniform heat removal rate, and the area-averaged Nusselt number was slightly lower. Therefore, the sweeping jet and film composite cooling caused the distribution of the flat plate heat transfer to be more uniform. It is worth noting that the novel direct jet nozzle in the present work had considerable area-averaged impingement cooling effectiveness.